A Case of Primary Hepatic Neuroendocrine Tumor and Literature Review - Pak Chiu Wong; Wong Hoi She; Ui Soon Khoo; Tan To Cheung (Case Reports in Oncology, 2021)
We report an unusual presentation of primary hepatic neuroendocrine tumor which was initially misdiagnosed as intrahepatic cholangiocarcinoma. The diagnosis was only revealed after a major liver resection by histopathology. With adjuvant lanreotide injection, the patient survived for more than 16 months after the operation without tumor recurrence. Diagnosis of this rare tumor has been a major challenge and we emphasize the importance of a preoperative diagnosis. Surgical resection remains the mainstay for curative treatment, while peptide receptor radionuclide therapy is an emerging treatment option which has provided promising results.